Autism and normative sexual development: a narrative review. Issue 23 (21st September 2013) - Dewinter, Jeroen; Vermeiren, Robert; Vanwesenbeeck, Ine; van Nieuwenhuizen, Chijs
Abstract : Aims and objectives: To explore the existing knowledge on sexuality and autism spectrum disorders. To this end, the concept of normative sexual development was used as an organising framework. Background: Sexual health can be seen as a developmental task for all children, adolescents and adults. Core autism features are related with skills central to sexual development and functioning. More insight in sexual development in people with autism is relevant for education, support and interventions by parents and professionals in somatic and mental health care. Methods: A comprehensive search of scientific online databases and reference lists was conducted. Publications based on qualitative and quantitative research, including case studies, were selected. Results: Fifty‐five articles and reports were selected and discussed. Information was grouped according to three domains: sexual behaviour, sexual selfhood and sexual socialisation. Conclusion: Sexual development is a part of life for people with autism of all developmental levels and is generally understudied in this population. Most information was available on behavioural aspects and experiences of socialising agents, such as parents and professionals. Developmental processes and the relation between sexual behaviour, selfhood and socialisation remained unclear. Relevance to clinical practice: Nurses working in schools, institutions and general health care support children, adolescents and adults with autism and advice their families, teachers, other educators and caregivers on sexuality issues. They can have an important role in daily assessment and support of this developmental domain by actively enquiring about the different aspects of sexual development and by offering information. Our findings offer an overview on the existing knowledge and support the idea that sexual development is normative for people with autism just as for anybody else.